Continuities and Transformations in Art, Manuscript Culture, and Architecture - Reilly, Diane (Rethinking Reform in the Latin West, 10th to Early 12th Century, 2023)

Reims, Liège, and Institutional Reform in the Central Middle Ages: Flavius Josephus as a Father of the Church - Reilly, Diane (Medieval Liège at the Crossroads of Europe. Monastic Society and Culture, 1000-1300, 2017)
(als e-book: 978-2-503-56897-3)

Gerardus Cameracensis. Acta Synodi Atrebatensis, Vita Autberti, Vita Gaugerici, Varia scripta ex officina Gerardi exstantia - Vanderputten, Steven; Reilly, Diane (Corpus Christianorum Continuatio Mediaevalis, 2014)
Keywords: Tekstuitgave

The Monastic World View in the Artistic Tradition - Reilly, Diane (Ecclesia in medio nationis. Reflections on the Study of Monasticism in the Central Middle Ages. Réflexions sur l’étude du monachisme au moyen âge central, 2011)